Education and Unemployment in Israel, 1976-1994: Reducing the Anomaly - Weisberg, Jacob; Meltz, Noah (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1999)
In industrialized economics, unemployment rates are inversely related to education levels. Data from 1963 to 1994 show that Israël is an anomaly exhibiting an inverted U-shaped relationship. Workers with 9-12 years of schooling consistently experienced a higher level of unemployment than the schooling groups with less and more education. Multivariate regression analysis of data for Israël during the 1976-1994 period indicates that this inverted U-shaped relationship is moderating. The national unemployment rate and a time trend variable had positive and significant effects tending to strengthen the inverted U-shaped relationship. However, an increase in the unemployment rate within the 0-8 education group relative to the 9-12 group and a decline in the labour force participation rate of the 0-8 group overrode these factors, resulting in a flattening of the inverse relationship. The major factor responsible for the anomaly in the education-unemployment relationship in Israël appears to be government policies intended to protect low-educated immigrants with large familles. A reduction in government support over recent years seems to have increased the exposure of the least educated to labour market forces.